2021
DOI: 10.1136/bmjopen-2020-045572
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hospital admissions from individual patient data (IPD): an applied example to explore key elements driving external validity

Abstract: ObjectiveTo explore factors that potentially impact external validation performance while developing and validating a prognostic model for hospital admissions (HAs) in complex older general practice patients.Study design and settingUsing individual participant data from four cluster-randomised trials conducted in the Netherlands and Germany, we used logistic regression to develop a prognostic model to predict all-cause HAs within a 6-month follow-up period. A stratified intercept was used to account for hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Sensitivity analysis indicated that intervention status had an impact on the model’s outcome. A general challenge to external model validation in different study cohorts has already been identified in the prediction of hospital admissions in PROPERmed [ 32 ]. In our case, this may be partly explained by differences in the inclusion criteria and in the baseline risk of patients from the development and validation datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analysis indicated that intervention status had an impact on the model’s outcome. A general challenge to external model validation in different study cohorts has already been identified in the prediction of hospital admissions in PROPERmed [ 32 ]. In our case, this may be partly explained by differences in the inclusion criteria and in the baseline risk of patients from the development and validation datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the binational PROPERmed database were used in model development and validation. In PROPERmed, individual participant data from five German and Dutch cluster-randomized controlled trials (cRCTs) were combined for pooled modelling purposes [30][31][32]. For this study, variables on ACh symptoms, a history of falls, and cognitive function were additionally taken from the studies.…”
Section: Source Of Datamentioning
confidence: 99%